2024
DOI: 10.33649/pusaka.v3i1.78
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kompetensi Profesional, Sarana Prasarana dan Motivasi Berprestasi Terhadap Kinerja Dosen

Abstract: The study aims at discovering the influence of professional competence, the influence facility and infrastructure on the performance of lecturers, the influence of achievement motivation at Tourism Polytechnic of Makassar. Data collection techniques employed observation, questionnaire, documentation, and interview. The number of samples in this study were 147 people consisting of lecturers and teaching staff with a sample of 114 people. The data analysis technique used is multiple linear regression analysis us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Achievement motivation in education is a combination of three factors, namely: educational success factors, success in carrying out the task and experience of success/failure in carrying out tasks 12 . Based on the description above, it can be concluded that achievement motivation is an encouragement that comes from within people to excel and try to achieve in an effort to achieve goals.…”
Section: The Effect Of Achievement Motivation On Job Satisfactionmentioning
confidence: 99%
“…Achievement motivation in education is a combination of three factors, namely: educational success factors, success in carrying out the task and experience of success/failure in carrying out tasks 12 . Based on the description above, it can be concluded that achievement motivation is an encouragement that comes from within people to excel and try to achieve in an effort to achieve goals.…”
Section: The Effect Of Achievement Motivation On Job Satisfactionmentioning
confidence: 99%
“…Thus, the performance of employees in an organization will increase. Research conducted by Sambung et al (2012), Pratama (2014), Hafid and Fajariani (2019a), Permanasari et al (2014), Fajduani et al (2021, Novita and Yulianti (2020), Arif et al (2021), Waterkamp et al (2018, Bolung et al (2018), and Bhagya (2020) stated that there is a positive relationship between professionalism and employee performance in a company. If all employees have a good OCB spirit, all work can be completed properly, and the company's performance will increase.…”
Section: Introductionmentioning
confidence: 99%
“…Lingkungan di kampus yang kondusif akan banyak berpengaruh pada hasil belajar mahasiswa. Dosen dan mahasiswa sangat membutuhkan lingkungan kerja yang kondusif untuk menumbuhkan dorongan dari dalam diri untuk lebih termotivasi dalam bekerja dan belajar (Arif, et al, 2021). Hal ini menunjukkan bahwa lingkungan kerja di kampus berkaitan dengan tinggi rendahnya kepuasan bagi seluruh warga di kampus khususnya para mahasiswa yang selalu melaksanakan perkuliahan di lingkungan kampus.…”
unclassified